Organizing blog as student’s diary: A teacher’s strategy to teach writing a recount text to junior high school students - Al Araf Amala (English Language Teaching and Research, 2020)
Internet is one of the on-line media that can be accessible for everybody in any places and moment. The development of this technology (IPTEK) gives positive impacts to education, especially in English writing class. In addition, some Junior High Schools and Senior High Schools have already got the multimedia room equipped by computer and internet connection. One of the ways to improve the students’ writing quality and the ability to write is through utilizing IPTEK development by organizing Blog (on-line journal). Blog is an on-line journal where the students can write anything that they are interested in, edit their writing and publish it, and even make a sharing media for their members. It hopes that writing through organizing blog will create a real and potential audience to improve the students’ writing, innovation, exploration, and better creation to give a better dynamic interaction, a better literacy, and even a better development work in team. This paper explains how to organize the on-line writing media such as blog to improve the students’ writing ability. The paper begins to explain about some problems faced by teachers at schools and theories of writing, diary, and blog. It also explains about the model of teaching writing through blog. The writer hopes that this technique can be applied and therefore it can help the teacher to teach writing in the class as away to improve their writing ability.